Mind over matter? Multinational naval interoperability during Operation Iraqi Freedom. Issue 1 (2nd January 2020) - Paget, Steven
ABSTRACT: The increasing frequency of multinational operations has heightened the importance of interoperability. While human and cultural factors are only two pieces of the interoperability jigsaw they are of enduring significance. The cohesiveness of the relationship amongst the Royal Australian Navy, the Royal Navy and the United States Navy during the 2003 Iraq War was underpinned by high levels of perceptive interoperability, which manifested itself in effective working relationships. That conflict demonstrated that while historical ties provided a foundation for cooperation, a number of multinational initiatives were undertaken to further enhance interoperability. This article addresses how such a high level of perceptive interoperability was achieved by examining the conduct of multinational exercises, the importance of personnel exchanges and the role of liaison officers, before considering the effect it had on the conduct of operations. The Iraq War demonstrated that cultural factors are at least as important as other facets of interoperability.